Novel Autosomal Recessive Nonsyndromic Hearing Impairment Locus DFNB90 Maps to 7p22.1-p15.3 - Ali, Ghazanfar (S. Karger AG, 2011)
A novel locus DFNB90 was mapped to 7p22.1-p15.3 by carrying out a genome scan in a multigenerational consanguineous family from Pakistan with autosomal recessive nonsyndromic hearing impairment (ARNSHI).DFNB90 is the eighth ARNSHI locus mapped to chromosome 7. A multipoint LOD score of 4.0 was obtained at a number of SNP marker loci spanning from rs1468996 (chromosome 7: 5.7 Mb) tors957960 (chromosome 7: 18.8 Mb). The 3-unit support interval and the region of homozygosity for DFNB90 spans from markers rs1553960 (chromosome 7: 4.9 Mb) to rs206198 (chromosome 7: 20.3 Mb). Candidate genes ACTB, BZW, OCM, MACC1, NXPH1, PRPS1L1, RAC1 and RPA3, which lie within the DFNB90 region, were sequenced and no potentially causal variants were identified.